Crisis u oportunidad: impacto de la migración venezolana en la productividad colombiana (2020)
The Venezuelan migration to Colombia, caused by the economic, political, and social crisis facing the country, has mobilized nearly 1.8 million people including Colombian returnees and Venezuelan migrants to Colombia. In this paper, we seek to compare the contributions to productivity between the Venezuelan employed migrant population and the non-migrant population, according to educational level, by geographic department and economic sector in Colombia. Using a panel data with fixed effects, we estimated the difference in the contribution to productivity of the migrant and non-migrant population for two periods of time, 2013-2016 and 2017-2019. During the first migration wave we found, on average, that migrant population with high and low educational levels had greater contributions to productivity than non-migrant population with low educational levels. For the second wave, no statistically significant effects were found. There is a possible self-selection bias given that migrants sought to work in the departments with higher levels of productivity.